Evaluating the time toxicity of cancer treatment in the CCTG CO.17 randomized clinical trial (RCT). Issue 28 (1st October 2022) - Gupta, Arjun; O'Callaghan, Christopher J.; Zhu, Liting; Jonker, Derek J.; Wong, Ralph; Colwell, Bruce; Moore, Malcolm J; Karapetis, Christos Stelios; Tebbutt, Niall C; Shapiro, Jeremy David; Tu, Dongsheng; Booth, Christopher M.
Abstract : 248 Background: Most individual treatments for advanced cancer are associated with modest survival benefits. The time spent in pursuing these treatments can be substantial. We have previously developed a pragmatic and patient-centered metric of these time costs, which we term ''time toxicity'', as any day with physical healthcare system contact. This includes outpatient visits (e.g., for bloodwork, scans, infusions, urgent care), emergency room visits, and overnight stays in a healthcare facility. Herein we sought to assess time toxicity in a completed RCT. Methods: We conducted a secondary analysis of the Canadian Cancer Trials Group CO.17 RCT that evaluated weekly cetuximab infusions vs supportive care alone in 572 patients with advanced colorectal cancer. CO.17 recruited participants in Canada, Australia and New Zealand. Initial results reported a 6-week improvement in median overall survival (OS) with cetuximab (6.1 vs 4.6 months, p = 0.005). Subsequent analyses reported that OS benefit was restricted to and significantly more in patients with K-ras wild-type tumors. We calculated patient-level time toxicity by analyzing treatment, follow-up, and resource utilization forms. We considered a day without physical healthcare contact as a ''home day''. Thus, for a patient, OS was time toxic days + home days. We compared medians of time measures across arms, and stratified results by K-ras status. Results: In the overall population, median time toxic days were higher in the cetuximab arm (28, vs 10, p < 0.001), although median home days were not statistically different (140, vs 121, p = 0.09). The proportion of time toxic days (time toxic days/OS) were significantly more with cetuximab (18%, vs 6%, p < 0.001). Of the 28 time toxic days in the overall cetuximab arm, 14 (50%) were protocol-related (e.g., scheduled infusions etc). Stratified results are in the table. Conclusions: Time toxicity can be extracted through secondary analyses of RCTs. In CO.17, despite an overall OS-benefit with cetuximab, home days were statistically similar across arms. In the K-ras-mutated group, cetuximab was associated with numerically similar OS but more time toxic days. In the K-ras-wild type group, cetuximab was associated with higher home days. Thus, time toxicity data need not always be sobering. Time toxicity measures can supplement traditional survival endpoints in RCTs to guide patient-oncologist decision-making. Cooperative group RCTs are well positioned for such analyses. Clinical trial information: NCT00079066. Measure (median) Cetuximab Supportive care alone P-Value Overall n = 287 n = 285  OS 6.1 months 4.6 months 0.005  Time toxic days 28 10 < 0.001  Home days 140 121 0.09  % time toxic days 18% 6% < 0.001 K-ras-mutated n = 81 n = 83  OS 4.5 months 4.6 months 0.089  Time toxic days 23 11 < 0.001  Home days 114 112 0.571  % time toxic days 16% 8% < 0.001 K-ras-wild type n = 117 n = 113  OS 9.5 months 4.8 months < 0.001  Time toxic days 41 10 < 0.001  Home days 186 132 < 0.001  % time toxic days 18% 6% < 0.001